Integration of Augmented Reality and Motion Capture Technology in the Development of Interactive Animation Based on the Digital Story of Malin Kundang - Joko Sutopo; Anggita Taalungan; Charles De Haan; RB Hendri Kuswantoro; Abdul Syukor Mohamad Jaya (Yayasan Keluarga Guru Mandiri, 2025)
The folk tale of Malin Kundang carries significant moral and cultural values, yet younger generations' interest in conventional storytelling has declined with the advancement of digital technologies. This research addresses that gap by developing an interactive digital animation using Augmented Reality (AR) and Motion Capture (MoCap) technologies to create a more immersive and engaging user experience. Through a mixed-methods approach, including prototype development with Unity 3D, motion tracking using OptiTrack/Xsens, and user testing, the system achieved 95% accuracy in character motion and high user satisfaction. While technical challenges such as latency and hardware constraints remain, the results demonstrate that the integration of AR and MoCap revitalizes traditional stories and offers global benefits—providing scalable solutions applicable to education, cultural heritage preservation, training simulations, and entertainment industries worldwide. This study contributes to the growing field of immersive digital storytelling and offers insights for future research into motion algorithm optimization and developing more accessible MoCap technologies for global use.